What Barriers? What Bridges? - Holling, C.S. (Barriers and Bridges to the Renewal of Ecosystems and Institutions, 1995)
This volume uses a series of case studies to test an emerging theory o f complex adaptive systems that forms the basis for explaining the int errelated dynamics of ecosystems, institutions and society. It deals e qually with institutional organization and ecosystem structure.